Factors affecting the results of national nursing license examination among newly graduated nurses in a private nursing college, Thailand: A mixed methods research - Oatme, Sakawduean; Waropastrakul, Nariporn; Sarnkhaowkhom, Chawapon (Science, Engineering and Health Studies, 2021)
This research aimed to study the factors affecting the results of national nursing license examination among newly graduated nurses by applying a mixed methods approach. The sample consisted of 113 newly graduated students from Saint Louis College in Thailand in the academic year of 2018. Data were collected through questionnaire, group discussion, and in-depth interview. Quantitative data were analyzed with regression method, whereas the qualitative data were analyzed using content analysis. The results of this study showed that 65 (57.52%) newly graduated nurses passed the national nursing license examination in all subjects during the first round. Cumulative grade point averages (GPA) and the results of the comprehensive examination predicted the results of the national nursing license examination (p<0.05). Qualitative data indicated the students’ motivation for exam preparation comes from a sense of responsibility toward their family and peer pressure, and the most common reason for failing the exam was due to recklessness. The students stated that the preparation program for the exam was suitable. Factors that led to passing the national nursing license examination were help from friends, time management, and personal characteristics. However, the libraries, dormitories, and activity spaces were not conducive to exam preparation.